2017
DOI: 10.1038/srep44475
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding disentanglement of multipartite entangled optical beams with a correlated noisy channel

Abstract: A quantum communication network can be constructed by distributing a multipartite entangled state to space-separated nodes. Entangled optical beams with highest flying speed and measurable brightness can be used as carriers to convey information in quantum communication networks. Losses and noises existing in real communication channels will reduce or even totally destroy entanglement. The phenomenon of disentanglement will result in the complete failure of quantum communication. Here, we present the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…The three-mode GHZ state is obtained by combining a phasesqueezed and two amplitude-squeezed states using two beam splitters with transmissivities of T 1 = 1/3 and T 2 = 1/2, respectively, as shown in Fig. 1d [30]. Similarly, the fourmode square Gaussian cluster state is prepared by coupling two phase-squeezed and two amplitude-squeezed states on a beam-splitter network consisting of three beam splitters with T 3 = 1/5 and T 4 = T 5 = 1/2, respectively, as shown in Fig. 1e [31].…”
Section: Methodsmentioning
confidence: 99%
“…The three-mode GHZ state is obtained by combining a phasesqueezed and two amplitude-squeezed states using two beam splitters with transmissivities of T 1 = 1/3 and T 2 = 1/2, respectively, as shown in Fig. 1d [30]. Similarly, the fourmode square Gaussian cluster state is prepared by coupling two phase-squeezed and two amplitude-squeezed states on a beam-splitter network consisting of three beam splitters with T 3 = 1/5 and T 4 = T 5 = 1/2, respectively, as shown in Fig. 1e [31].…”
Section: Methodsmentioning
confidence: 99%
“…Decoherence effects on entangled state has been well studied [42][43][44][45][46][47]. It has been shown that two entangled qubits become completely separable in a finite-time under the influence of vacuum which is the so called entanglement sudden death [42,43], and disentanglement occurs in Gaussian multipartite entangled states when one mode is transmitted in a noisy channel [48]. It is essential to recover entanglement when entanglement sudden death happens.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to recover entanglement when entanglement sudden death happens. A number of methods to recover the destroyed entanglement have been demonstrated, such as the non-Markovian environment [48][49][50], weak measurement [51] and feedback [52]. Since EPR steering is so intriguing and has enormous potential in quantum communication applications, it is imperative and significant to investigate the influence on Gaussian EPR steering made by decoherence.…”
Section: Introductionmentioning
confidence: 99%
“…Since any manipulation of quantum systems requires them to be in contact with a noisy environment, a major question in advancing control upon them -arguably the main directive towards the development of functional quantum technologies -is how we can preserve this phenomenon for as long as it takes for an experiment to unfold. The design and application of quantum control techniques aimed at sustaining the entanglement of quantum systems has thus been a lively area of work over the last fifteen years [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] that has seen the exploration of open-loop [2,7] as well as measurement-based [3][4][5][6][8][9][10] and quantum coherent feedback [13] strategies, applicable in principle to a wide variety of systems, although quantum optical scenarios seem to offer accurate enough control and low enough noise to facilitate such endeavours [1,11,16].…”
Section: Introduction and Background: The Control Of Quantum Entanmentioning
confidence: 99%
“…In this paper, we address the open-loop control of Gaussian entanglement, such as the one displayed in experiments based on parametric down conversion processes [11,12,16]. As well as providing an insightful theoretical landscape where, as we shall see, much can be evaluated analytically even when realistic noise is included, Gaussian systems are widely applicable not only to optical set-ups, but also in all other situations where the interaction between constituents and with the environment may be linearised, e.g.…”
Section: Introduction and Background: The Control Of Quantum Entanmentioning
confidence: 99%